The Impact of Western Civilization on Forests in Barkskins - Shrestha, Ravi Kumar (Pursuits: A Journal of English Studies, 2023)
This research article very critically scrutinizes how forests in North America are devastated by the growing human civilization. It deals with ecological degradation in an American novelist Annie Proulx’s novel Barkskins whose location is North America. In course of analysing the novel critically, the article describes how Barkskins revolves round the story of white colonists and indigenous Indians in North America or today’s Canada. Firstly, it reveals how two families: Sel family (a poor biracial family of French and Mi’kmaq) that cuts trees and Duke family (rich French family) that does business of fur are linked to trees and deforestation. Secondly, the article focuses on the impact of western civilization on forests regarding forests as the antagonist to western civilization. Western colonialism is also a vehicle of civilization that causes deforestation. Due to civilization, humanism is developed. So, anthropocentric nature of people causes deforestation. Thirdly, European civilization has a negative impact on Indigenous people and their culture. Apparently, forests are shown as a symbol of darkness, evil forces, backwardness and an obstacle for human progress, but in the name of civilization, whites do deforestation due to their greed of colonization and anthropocentric nature. Hence, the first objective of the research is to explore why the whites regard forests as the antagonist to civilization. Likewise, the second objective of the article is to discover the real cause of them to do deforestation. Besides, as for the broad theoretical methodology, Greg Garrard’s theory of Ecocriticism is applied for the textual analysis of Barkskins since the article deals with the ecological destruction of North America by whites and ecocriticism has emerged as a response to the heavy damage done to ecology by human beings.